ANALYSIS OF PHYSICAL EDUCATION INSTRUCTION USING ASYNCHRONOUS METHOD ON A DISTANCE LEARNING SYSTEM - Leli Rahman; Taufik Rihatno; Fatah Nurdin (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This study aims to find out how the level of learning activity using the method asynchronous in distance learning. The research method uses descriptive analysis method. The research population was students of SMAN 1 Cisarua in the 2020/2021 academic year with a total sample of 90 people, while the instrument used in this study was a learning activity questionnaire. The data analysis technique used relative frequency distribution and trend test. The results showed that the